Supporting families of children with disabilities – the prospect of change - Żyta, Agnieszka; Ćwirynkało, Katarzyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The paper includes the summary of changes that take place in the field of social support given to families of children with disabilities in Poland and abroad. In the empirical part, using in-depth interviews, this study investigated the personal experiences of 11 mothers of children with Down syndrome within the social support system. Interview transcripts were qualitatively analysed with the usage of interpretative phenomenological analysis. Several themes emerged: support concentrated on a child with a disability as well as instrumental, informative, emotional support of parents (both formal and informal). Parents described various sources of the received support but also mentioned their shortcomings. The importance of adapting the modern model of supporting families of children with disabilities is highlighted and the implications of the findings are discussed.
Keywords: supporting; disability; family; Down syndrome